Dual DNA Transfection Using 1,6-Hexanedithiol-Conjugated Maleimide-Functionalized PU-PEI600 For Gene Correction in a Patient iPSC-Derived Fabry Cardiomyopathy Model - Chien, Chian-Shiu; Chien, Yueh; Lin, Yi-Ying; Tsai, Ping-Hsing; Chou, Shih-Jie; Yarmishyn, Aliaksandr A.; Rastegari, Elham; Wang, Ting-Xian; Leu, Hsin-Bang; Yang, Yi-Ping; Wang, Mong-Lien; Jheng, Ying-Chun; et al. (Frontiers in Cell and Developmental Biology, 2021)
Non-viral gene delivery holds promises for treating inherited diseases. However, the limited cloning capacity of plasmids may burden the concurrent delivery of distinct genes to the transfected cells. Previously, the conjugation of maleimide-functionalized polyurethane grafted with small molecular weight polyethylenimine (PU-PEI600-Mal) using 1,6-hexanedithiol (HDT) was demonstrated to promote the concurrent delivery and extensive co-expression of two different plasmids in target cells. Herein, we used HDT-conjugated PU-PEI600-Mal to concurrently deliver all CRISPR/Cas9 components to achieve efficient gene correction in an induced pluripotent stem cell (iPSC)-derived model of Fabry cardiomyopathy (FC) with GLA IVS4+919 G>A mutation. This FC in vitro model recapitulated various clinical FC features, including cardiomyocyte hypertrophy and lysosomal globotriaosylceramide (Gb3) deposition. As evidenced by expression of two reporter genes, GFP and mCherry, the addition of HDT conjugated two distinct PU-PEI600-Mal/DNA complexes and promoted the concurrent delivery of sgRNA/Cas9 and homology-directed repair DNA template into target cells to achieve effective gene correction of IVS4+919 G>A mutation. PU-PEI600-Mal/DNA with or without HDT-mediated conjugation consistently showed no cytotoxicity and did not affect cardiac induction of transfected FC-iPSCs. After gene correction and cardiac induction, disease features, including cardiomyocyte hypertrophy, upregulation of hypertrophy-associated genes, and Gb3 deposition, were remarkably corrected in the FC-iPSC-differentiated cardiomyocytes. Collectively, this dual DNA transfection system based on HDT-conjugated PU-PEI600-Mal may be an ideal solution to improve the concurrent transfection of non-viral-based gene editing system in inherited diseases with specific mutations.